Spatio-Temporal Optical Coherence Imaging – a new tool for in vivo microscopy - Wojtkowski, Maciej; Stremplewski, Patrycjusz; Auksorius, Egidijus; Borycki, Dawid (Photonics Letters of Poland, 2019)
Optical Coherence Imaging (OCI) including Optical Coherence Tomography (OCT) and Optical Coherence Microscopy (OCM) uses interferometric detection to generate high-resolution volumetric images of the sample at high speeds. Such capabilities are significant for in vivo imaging, including ophthalmology, brain, intravascular imaging, as well as endoscopic examination. Instrumentation and software development allowed to create many clinical instruments. Nevertheless, most of OCI setups scan the incident light laterally. Hence, OCI can be further extended by wide-field illumination and detection. This approach, however, is very susceptible to the so-called crosstalk-generated noise. Here, we describe our novel approach to overcome this issue with spatio-temporal optical coherence manipulation (STOC), which employs spatial phase modulation of the incident light. Full Text: PDF References L. Wang, P. P. Ho, C. Liu, G. Zhang, and R. R. Alfano, "Ballistic 2-D Imaging Through Scattering Walls Using an Ultrafast Optical Kerr Gate", Science 253, 769-771 (1991). CrossRef D. Huang, E. A. Swanson, C. P. Lin, J. S. Schuman, W. G. Stinson, W. Chang, M. R. Hee, T. Flotte, K. Gregory, C. A. Puliafito, and et al., "Optical coherence tomography", Science 254, 1178-1181 (1991). CrossRef J. A. Izatt, E. A. Swanson, J. G. Fujimoto, M. R. Hee, and G. M. Owen, "Optical coherence microscopy in scattering media", Opt. Lett. 19, 590-592 (1994). CrossRef D. Borycki, M. Nowakowski, and M. Wojtkowski, "Control of the optical field coherence by spatiotemporal light modulation", Opt. Lett. 38, 4817-4820 (2013). CrossRef D. Borycki, M. Hamkalo, M. Nowakowski, M. Szkulmowski, and M. Wojtkowski, "Spatiotemporal optical coherence (STOC) manipulation suppresses coherent cross-talk in full-field swept-source optical coherence tomography", Biomed. Opt. Express 10, 2032-2054 (2019). CrossRef P. Stremplewski, E. Auksorius, P. Wnuk, L. Kozon, P. Garstecki, and M. Wojtkowski, "In vivo volumetric imaging by crosstalk-free full-field OCT", Optica 6, 608-617 (2019). CrossRef L. Vabre, A. Dubois, and A. C. Boccara, "Thermal-light full-field optical coherence tomography", Opt. Lett. 27, 530-532 (2002). CrossRef M. Laubscher, M. Ducros, B. Karamata, T. Lasser, and R. Salathé, "Video-rate three-dimensional optical coherence tomography", Opt. Express 10, 429-435 (2002). CrossRef Dubois and A. C. Boccara, Full-Field Optical Coherence Tomography, (Springer Berlin Heidelberg, Berlin, Heidelberg, 2008), pp. 565-591. CrossRef O. Thouvenin, K. Grieve, P. Xiao, C. Apelian, and A. C. Boccara, "En face coherence microscopy [Invited]", Biomedical Opt. Express 8, 622-639 (2017). CrossRef F. Fercher, C. K. Hitzenberger, M. Sticker, E. Moreno-Barriuso, R. Leitgeb, W. Drexler, and H. Sattmann, "A thermal light source technique for optical coherence tomography", Optics Commun. 185, 57-64 (2000). CrossRef R. A. Leitgeb, "En face optical coherence tomography: a technology review [Invited]", Biomed Opt Express 10, 2177-2201 (2019). CrossRef J. Fujimoto and W. Drexler, Introduction to Optical Coherence Tomography, (Springer, Berlin, Heidelberg, 2008), pp. 1-45. CrossRef J. A. Izatt, M. A. Choma, and A.-H. Dhalla, Theory of Optical Coherence Tomography, (Springer International Publishing, Cham, 2015), pp. 65-94. CrossRef